2009
DOI: 10.1002/pbc.21932
|View full text |Cite
|
Sign up to set email alerts
|

123I‐mIBG scintigraphy in patients with known or suspected neuroblastoma: Results from a prospective multicenter trial

Abstract: This prospective multicenter trial of (123)I-mIBG scintigraphy documents high sensitivity and specificity of this imaging technique in patients with both newly diagnosed and previously treated neuroblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(64 citation statements)
references
References 21 publications
1
52
0
11
Order By: Relevance
“…In the past several years, many radiopharmaceuticals, including metaiodobenzylguanidine (MIBG), that were formerly labeled with 131 I are now labeled with 123 I because it has better dosimetric and imaging properties (1)(2)(3). 123 I decays by electron capture, with a 13.2-h half-life.…”
mentioning
confidence: 99%
“…In the past several years, many radiopharmaceuticals, including metaiodobenzylguanidine (MIBG), that were formerly labeled with 131 I are now labeled with 123 I because it has better dosimetric and imaging properties (1)(2)(3). 123 I decays by electron capture, with a 13.2-h half-life.…”
mentioning
confidence: 99%
“…In non-paediatric institutions, because of the longer time required for young children with additional sedation, and increased expense, they may not be regularly obtained. In the study by Vik et al (2009), SPECT views only marginally increased the sensitivity from 88 to 91%. Although additional information was gained in 65% of cases regarding the precise anatomic location of uptake, Curie scores would not have been substantially altered.…”
mentioning
confidence: 74%
“…A recent study using blinded readers and concomitant pathology, CT scan and clinical information showed that 123 I-mIBG scintigraphy had a sensitivity of 88% and a specificity of 83% (Vik et al, 2009). Occasionally, false-positive readings may occur because of uptake in mature ganglioneuroma or other neuroendocrine tumours, or because of physiological uptake that may be mistaken for tumour in the adrenal gland, salivary gland, nasopharynx, brown fat or excretion through renal pelvis and bladder (Pfluger et al, 2003).…”
mentioning
confidence: 99%
“…MIBG, an analog of norepinephrine and a guanethidine derivative, is taken up and stored in NB cells expressing the norepinephrine transporter and is radio-iodinated for imaging use (Boubaker & Bischof Delaloye, 2008). MIBG scan has a reported sensitivity and specificity of 88% and 83%, respectively (Vik et al, 2009). In comparison, 99m Tc-technetium bone scan is reported to have a sensitivity of 75% and specificity of 50% for the detection of skeletal metastases (Jacobs et al, 1990).…”
Section: Metastatic Diseasementioning
confidence: 99%